2019
DOI: 10.2967/jnumed.118.221994
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility and Comparability of Preclinical PET Imaging Data: A Multicenter Small-Animal PET Study

Abstract: The standardization of preclinical imaging is a key factor to ensure the reliability, reproducibility, validity, and translatability of preclinical data. Preclinical standardization has been slowly progressing in recent years and has mainly been performed within a single institution, whereas little has been done in regards to multicenter standardization between facilities. This study aimed to investigate the comparability among preclinical imaging facilities in terms of PET data acquisition and analysis. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 33 publications
4
34
0
Order By: Relevance
“…In addition to biological, anesthesia-related and animal handling-related effects, quantification variations caused by the circadian rhythm can add-up with effects triggered by imaging workflow-specific quantification errors such as attenuation, partial volume effects or scatter 20 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to biological, anesthesia-related and animal handling-related effects, quantification variations caused by the circadian rhythm can add-up with effects triggered by imaging workflow-specific quantification errors such as attenuation, partial volume effects or scatter 20 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, multiple journals have updated their requirements for manuscript submission so that the respective authors either need to upload imaging data as well as all metadata, or to include a data availability statement during submission [130,131]. An open access of the imaging data and respective metadata is certainly a huge step toward transparency and increased reproducibility and reliability of the data [132], as it has been demonstrated that image analysis is highly user-and software-dependent [133]. Randomized preclinical multi-center studies have been proposed to overcome the lack of reproducibility due to inadequate sample size, low significance, and low confidence of data [134][135][136][137].…”
Section: Preclinical Hybrid Imagingmentioning
confidence: 99%
“…However, the potential of multi-center studies cannot be fully accessed without proper standardization techniques in place in each participating institute. A recent study focusing on utilizing a basic [18F]fluorodeoxyglucose ([18F]FDG) imaging protocol in 4 different institutes demonstrated that the comparability among multiple institutes might be hampered due to, e.g., animal handling (each institute had different fasting protocols of animals in place; temperature regulation of animals during acquisition differed significantly), and animal facility environment or image analysis [133].…”
Section: Preclinical Hybrid Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…At the time point of PET imaging, mean body weight of rats were 236 ± 33 g. The following standardized imaging setup was applied for all [ 18 F]FDG scans [19][20][21]. In brief, rats were deprived of food for 18 ± 4 h prior [ 18 F]FDG administration.…”
Section: Pet Imaging Proceduresmentioning
confidence: 99%